Profil Darah Rusa Totol (Axis axis) Betina Sehat di Pusat Inovasi Agroteknologi (PIAT), Universitas Gadjah Mada - Adji, Dhirgo; Astuti, Dian (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2020)
Center for Agrotechnology Innovation, Gadjah Mada University (PIAT), one of the place for development and breeding ground of spotted deer in Yogyakarta, Indonesia. The study of blood profiles was intended to allow veterinarian to understand the normal profile of the spotted deer. Fifteen healthy spotted deers belonging to PIAT were used as experimental animals. The deers were drawn its blood through the jugular vein without the use of anaesthesia. Blood was then accommodated in an EDTA tube, centrifuged at 2500 RPM and analyzed using a Mindray BC-2800 haematology analyzer machine. Based on the results of the study of the blood it were known that Haemoglobine (Hb) was: 11.5 ± 1.703 g/dl, Red blood cells (RBC) was: 9.3 ± 3.580 106/µl, Packed cell volume (PCV) was: 30.8 ± 6.035 %, Mean corpuscular Volume (MCV) was: 36.8 ± 11.102 fl, Mean corpuscular haemoglobine (MCH) was: 15.0 ± 7.313 pg, Mean corpuscular haemoglobine concentration (MCHC) was: 40.0 ± 14.657 g/dl, White blood cells (WBC) was: 6.4 ± 3.096 103/µl , Neutrophils was: 43.4 ± 21.646, % Basophils was: 0.2 ± 0.168 %, eosinophils was: 0.4 ± 0.447 %, lymphocytes was: 53.4 ± 21.546 % and monocytes was: 2.6 ± 2.394 %. From all of the datas it indicated that blood profiles of PIAT’s spotted deers are different from similar spotted deer blood profiles in India.